Combining interferon-γ release assays and metagenomic next-generation sequencing for diagnosis of pulmonary tuberculosis: a retrospective study - Yanyan Liu; Miaohong Fang; Chenxi Yuan; Yi Yang; Liang Yu; Yasheng Li; Lifen Hu; Jiabin Li (BMC Infectious Diseases)
Abstract Background Rapid diagnosis of pulmonary tuberculosis (PTB) is urgently needed. We aimed to improve diagnosis rates by combining tuberculosis-interferon (IFN)-γ release assays (TB-IGRA) with metagenomic next-generation sequencing (mNGS) for PTB diagnosis. Methods A retrospective study of 29 PTB and 32 non-TB patients from our hospital was conducted between October 2022 and June 2023. Samples were processed for TB-IGRA and mNGS tests according to the manufacturer’s protocol. Results The levels of IFN-γ release in PTB patients were significantly higher than those in non-TB patients (604.15 ± 112.18 pg/mL, and 1.04 ± 0.38 pg/mL, respectively; p < 0.0001). Regarding presenting symptoms or signs, cough and thoracalgia were less common in PTB patients than in non-TB patients (p = 0.001 and p = 0.024, respectively). Total protein and albumin levels in the sera of PTB patients were significantly elevated compared to non-TB patients (p = 0.039 and p = 0.004, respectively). The area under the ROC curve (AUC) for TB-IGRA in PTB diagnosis was 0.939. With an optimal IFN-γ cut-off value of 14.3 pg/mL (Youden’s index 0.831), sensitivity was 86.2% and specificity was 96.9%. ROC curve analysis for mNGS and TB-IGRA combined with mNGS showed AUCs of 0.879 and 1, respectively. The AUC of TB-IGRA combined with mNGS was higher than that of TB-IGRA and mNGS alone. Conclusions TB-IGRA combined with mNGS may be an effective method for diagnosing tuberculosis, and can be used in the clinical diagnosis of PTB.